Phytotherapy and Medicinal Plants in the Treatment of Dysmenorrhea: A Systematic Review Study in Iranian Ethnobotanical Documents - Roza Soltanifard; Somayeh Shahsavari; Pegah Shakib; Saber Abbaszadeh (Indian Journal of Forensic Medicine & Toxicology, 2021)
Dysmenorrhea is an unusual pain in the abdomen during menstruation. Women experience pain in the lowerabdomen and uterus during menstruation, but if the pain is too much to stop daily activities, it is calleddysmenorrhea or painful menstruation. Chemical treatments for dysmenorrhea are usually associated withside effects. Gastrointestinal problems, nausea, blurred vision, headache, and dizziness are some of theside effects of medications used to treat dysmenorrhea. Today, the use of herbal remedies and traditionalmedicine has become common. In this systematic review study, the most important medicinal plantsmentioned for dysmenorrhea in Iranian ethnobotanical documents were extracted and reported. In thisreview study, keywords such as dysmenorrhea, medicinal plants, ethnobotany, identification of medicinalplants, region and Iran from databases including ISI ,Web of Science, PubMed, Scopus, ISC, Magiran andGoogle Scholar to review articles and Resources used. Based on the obtained results, medicinal plantsFoeniculum vulgare Mill, Juniperus communis, Origanum vulgare, Salvia sclarea L., Urtica dioica L.,Anthemis cotula L., Carthamus lanatus L., Silybum marianum [L.] Gaerth., Anthriscus cerefolium L[Hoffm.], Vitex pseudonegundo, Parietaria judaica L., Achillea biebersteinii Afanasiev., Equisetum arvenseL., Phoeniculum vulgare Mill. daenensis Celak., Peganum harmala L., Trifolium repens L., Salix aegyptiacaL., Nepeta fassenii, Cicer kermanenses, Teucrium pollium L., Achillea santolina, Cuminum cyminum,Valeriana officinalis, Salvia macrosiphon, Achillea eriophora, which are medicinal plants. They are used indifferent regions of Iran to treat dysmenorrhea.